Causal relationship in gut microbiota and upper urinary urolithiasis using Mendelian randomization - Zhang, Ruiqiao; Zhao, Weijie; Zhao, Ruijie; Zhao, Yunhai; Zhang, Yanlong; Liang, Xuezhi (Frontiers in Microbiology, 2023)
Background Several reports in recent years have found an association between gut microbiota and upper urinary urolithiasis. However, the causal relationship between them remains to be clarified. Methods Genetic variation is used as a tool in Mendelian randomization for inference of whether exposure factors have a causal effect on disease outcomes. We selected summary statistics from a large genome-wide association study of the gut microbiome published by the MiBioGen consortium with a sample size of 18,340 as an exposure factor and upper urinary urolithiasis data from FinnGen GWAS with 4,969 calculi cases and 213,445 controls as a disease outcome. Then, a two-sample Mendelian randomization analysis was performed by applying inverse variance-weighted, MR-Egger, maximum likelihood, and weighted median. In addition, heterogeneity and horizontal pleiotropy were excluded by sensitivity analysis. Results IVW results confirmed that class Deltaproteobacteria (OR = 0.814, 95% CI: 0.666–0.995, P = 0.045), order NB1n (OR = 0.833, 95% CI: 0.737–0.940, P = 3.15 × 10−3), family Clostridiaceae1 (OR = 0.729, 95% CI: 0.581–0.916, P = 6.61 × 10−3), genus Barnesiella (OR = 0.695, 95% CI: 0.551–0.877, P = 2.20 × 10−3), genus Clostridium sensu_stricto_1 (OR = 0.777, 95% CI: 0.612–0.986, P = 0.0380), genus Flavonifractor (OR = 0.711, 95% CI: 0.536–0.944, P = 0.0181), genus Hungatella (OR = 0.829, 95% CI: 0.690–0.995, P = 0.0444), and genus Oscillospira (OR = 0.758, 95% CI: 0.577–0.996, P = 0.0464) had a protective effect on upper urinary urolithiasis, while Eubacterium xylanophilum (OR =1.26, 95% CI: 1.010–1.566, P = 0.0423) had the opposite effect. Sensitivity analysis did not find outlier SNPs. Conclusion In summary, a causal relationship was found between several genera and upper urinary urolithiasis. However, we still need further randomized controlled trials to validate.